GOALS, OBJECTIVES, MEANS, PRINCIPLES AND METHODS OF SPORTS TRAINING - Ashur Nazarovich Normurodov (Galaxy International Interdisciplinary Research Journal, 2023)
This is a process of sports improvement, the purpose of which is to lead him to high and record results in any sport through a systematic and systematic impact on the capabilities and preparedness of an athlete.